Tree Hazard Assessments at University Putra Malaysia Using GIS-Based UPM-MUTIS Decision Support System - Teng, Jonathan Yi Chuon (2011)
Urban forest can be defined as art, science and technology of managing trees and forest resources that grow within a city, town or a suburb. It provides benefits in the form of green landscape, storm water management, carbon storage which lead to human heath. Regardless, they are also potentially cause hazardous to their surroundings. Hence, there is a need to evaluate urban trees whether they are hazardous or not. These can be prevented by developing a tree information system which can determine hazardous trees as well as function as trees‟ coordinates‟ locator information storage. It also will act as decision support tool for the management. Hazard rating assessment in the context of urban trees is the evaluation of the defect severity of trees and how likely they are to fail as well as how severe in terms of damage that they could cause to their surroundings. In this study, roadside trees hazard rating was assessed automatically by a Visual Basic for Applications (VBA) in customized ArcMapTM application using, known as Universiti Putra Malaysia-Malaysian Urban Trees Information System (UPM MUTIS), developed by the Faculty of Forestry, UPM. The capabilities of UPM-MUTIS ver. 1.0 in determining hazard rating are also assessed. The study area covered part of UPM‟s academic zone. Result revealed that out of 909 trees assessed, A total of 840 trees (92.4%) were categorized as „Low‟ hazard rating, 67 trees (7.4%) as „Medium‟ hazard rating and no trees with „High‟ and „Severe‟ hazard rating. The accuracy on the tree counting in the study area is 95.15%. UPM-MUTIS should be further developed into a web-based system which can be accessed by all potential users. UPM-MUTIS should be further tested by local municipal council and arborists for practicality. Further studies should be done on UPM-MUTIS to enable life long monitoring of tree health and tree risk status that could change over time